1988
DOI: 10.1007/bf00043109
|View full text |Cite
|
Sign up to set email alerts
|

Callus growth and plant regeneration in diverse cultivars of cucumber (Cucumis sativus L.)

Abstract: The growth and differentiation of callus tissues derived from cotyledons of ten cultivars of Cucumis sativus L. were investigated. Cotyledonary explants from all ten cultivars formed callus tissue on Murashige and Skoog (MS) medium supplemented with 0.5 gM 2,4-dichlorophenoxyacetic acid and 5 #M 6-benzylaminopurine. Fresh weight of the callus tissues averaged 1 to 8 g per flask after five weeks of culture. Shoot development was achieved in three cultivars, Hukchinju, Manchoonchoungjang and Seoul, on MS medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
(13 reference statements)
4
22
2
Order By: Relevance
“…The maximum amount of embryogenic callus was obtained on MS medium supplemented with 3.0 mg L -1 of NAA. Similar kind of somatic embryogenic studies and shoot regeneration induction was reported in cucumber leaves (Usman et al 2011;Kim et al 1988;Ali et al 1991). Then the small piece of primary globular embryogenic callus was subcultured on MS medium supplemented with 2.5 mg L -1 BAP ?…”
Section: Effect Of Naa Alone or In Combination With Bap On Induction supporting
confidence: 69%
“…The maximum amount of embryogenic callus was obtained on MS medium supplemented with 3.0 mg L -1 of NAA. Similar kind of somatic embryogenic studies and shoot regeneration induction was reported in cucumber leaves (Usman et al 2011;Kim et al 1988;Ali et al 1991). Then the small piece of primary globular embryogenic callus was subcultured on MS medium supplemented with 2.5 mg L -1 BAP ?…”
Section: Effect Of Naa Alone or In Combination With Bap On Induction supporting
confidence: 69%
“…Differences in explant response among cultivars of the same species has been observed in cucumber, Cucumis sativus L . (Kim et al ., 1988), melon (Gray et al ., 1993 ;Niedz et al ., 1989), potato (Cardi et al ., 1993 ;M'Ribu & Veilleux, 1990), tomato 'Collective diameter of all 3 flexuous anthers per flower . Y Leaf length by width ratio ; obtained by dividing the leaf length by its width .…”
Section: Methodsmentioning
confidence: 99%
“…Variety of explants have been used as starting material for plant regeneration from cucumber, such as nodal segments (Ahmad & Anis, 2005), shoot tip (Vasudevan et al, 2001;Jafar & Nuray, 2007), cotyledons (Trulson & Shahin, 1986;Kim et al, 1988;Chee, 1990), hypocotyl explants (Rajasekaran et al, 1983;Ziv & Gadasi, 1986;Selvaraj et al, 2006), primary leaves (Chee & Tricoli, 1988;Malepszy & Nadolska-Orezyk, 1989;Seo et al, 2000), and petioles (Punja et al, 1990). Regeneration of cucumber is also possible through protoplast, leaf-derived callus (Abu-Romman et al, 2013), somatic embryogenesis (Chee, 1990), and cell suspension culture (Chee & Tricoli, 1988;Raharjo & Punja, 1992;Lou & Kako, 1994;Vengadesan et al, 2005;Ugandhar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%